Biopolymer Micro/Nanogel Particles as Smart Drug Delivery and Theranostic Systems - Susana C. M. Fernandes; Garbine Aguirre (MDPI AG, 2023)
In recent years, micro/nanogels have become an important topic of interdisciplinary research, especially in the fields of polymer chemistry and material science, with a focus on their use in drug delivery applications [...]